Student Attendance Information System Using Web-Based Nodemcu ESP8266 - Arif Sulistio; Ritzkal Ritzkal; Yuggo Afrianto (Institute of Computer Science (IOCS), 2020)
Presence or attendance in educational institutions such as Ibn Khaldun University Bogor is an important aspect in supporting the course of the lecture system, currently the attendance system at Ibn Khaldun University Bogor, especially in the Informatics Engineering study program, still uses a conventional system where students still have to sign an attendance sheet at the time lectures. In this study, there are two problem formulations (i) How to design and implement student attendance system devices using radio frequency identification (RFID) technology and WEB-based NodeMCU ESP8266, (ii) How to test WEB to display information on the presence of Informatics Engineering students using Black Box. The purpose of this study consisted of two stages (i) Designing and implementing a student attendance system device using radio frequency identification (RFID) technology and WEB-based NodeMCU ESP8266, (ii) being able to implement WEB testing to display information on the attendance of Informatics Engineering students using Black Box. Where in this study the framework has four stages, namely (i) analysis, (ii) design, (iii) implementation and (iv) testing. The results obtained in the research (i) Design and implementation of student attendance system devices using radio frequency identification (RFID) technology and WEB-based NodeMCU ESP8266 (ii) Implementation of WEB testing to display information on the presence of Informatics Engineering students using Black Box and get results appropriate.